Intramedullary brachytherapy for the treatment of long bone metastatic disease: A case report. Issue 2 (16th June 2023) - O'Neill, David Eric; Gannavarapu, Bhavani; Hrycushko, Brian; Folkert, Michael; Timmerman, Robert; Callan, Alexandra
Abstract: Case: A 56-year-old woman with metastatic melanoma and femoral lesions with impending pathologic fracture was indicated for intramedullary brachytherapy (IMBT) and intramedullary nail. Conclusions: IMBT + intramedullary nail is a new technique for the treatment of long bone metastases. IMBT maximizes radiation to the tumor and minimizes radiation to surrounding tissues. It allows the patient to resume systemic treatment expediently. Our cadaver model and patient were both treated for femoral metastases; however, this technique allows for the treatment of any long bone. This is a safe technique that minimizes treatment time compared with other standard radiation regimens.